[Book review] Eva Silvén, Friktion - Stoor, Krister (Journal of Northern Studies, 2024)
Review of: Eva Silvén, Friktion. Ernst Manker, Nordiska museet och det samiska kulturarvet, Lund: Nordic Academic Press 2021